The Impact of the Ideological and Religious Conflict on the Translation and Interpretation of the Holy Quran Case Study: The Sunni and Shia Interpretation and Translation - DZIRI, Fatima Zohra; KADRI, Hanane; BAKHOUCHE , Salah (Faculty of Letters and Foreign Languages Department of English, 2017)
Over centuries the sacred texts are the main religious principle that embodies the golden pillars of the divine message. The Quran is considered to be only true text when it is written in its original language. Thus translations are thought to lose the true meaning of the original words which are believed to be a direct revelation from God. The present study is an investigation of the ideological and religious implication on translating religious texts throughout discussing both religious translation and religious conflict. We tried to state the different religious texts‟ translation as key elements in transmitting the divine message, and then we tackled the techniques and strategies that used by translator to overcome the obstacles in the sacred texts. The conflict between Muslims, Christian, and Jews considered as the main factors that have an impact on religious translation. Sunni and Shia are the targeted samples to apply the investigation in order to achieve the desired aims. This study ends up with the belief that the conflict between Sunni and Shia can effect on the translation of the Holy Quran because of the different ideologies